Recent advances in optically induced di-electrophoresis and its biomedical applications. - Cai, Shuxiang; Ma, Zheng; Ge, Zhixing; Yang, Wenguang (Biomedical Microdevices, 2022)
The development of the micro/nano science and technology has promoted the evolvement of human civilization tremendously. The advancement of the micro/nano science and technology highly depends on the progress of the micro/nano manipulation techniques, and the micro/nano-scaled manipulation level is the critical sign of the micro/nano science and technology. This review, aimed at the demand and the challenge of the micro/nano material and biomedical fields and related to the scientific issues and implementation techniques of the optically induced di-electrophoresis (ODEP). We explained its working principle, manipulating method, and influencing factors of ODEP force to a certain extent. A number of application fields based-ODEP technology and specific applications so far are summarized and reviewed. Finally, some perspectives are provided on current development trends, future research directions, and challenges of ODEP.